2020
DOI: 10.1152/jn.00016.2020
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological markers of cochlear function correlate with hearing-in-noise performance among audiometrically normal subjects

Abstract: Hearing loss caused by noise exposure, ototoxic drugs or aging results from the loss of sensory cells, as reflected in audiometric threshold elevation. Animal studies show that loss of hair cells can be preceded by loss of auditory-nerve peripheral synapses, which likely degrades auditory processing. While this condition, known as cochlear synaptopathy, can be diagnosed in mice by a reduction of suprathreshold cochlear neural responses, its diagnosis in humans remains challenging. To look for evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 63 publications
1
56
1
3
Order By: Relevance
“…Such effects of noise which may be compounded by aging have been termed “hidden hearing loss” because they aren't detected by pure-tone audiometry (Liberman, 2020 ). Data from audiometrically normal adults shows that people with smaller auditory nerve or subcortical responses perform relatively poorly on hearing speech in the presence of background noise (Bharadwaj et al, 2015 ; Bramhall et al, 2015 ; Stamper and Johnson, 2015 ; Grant et al, 2020 ). However, this is still controversial as many studies in humans have failed to find significant relationships between speech perception and the amplitude of the auditory nerve action potential (Prendergast et al, 2017 ; Guest et al, 2018 ; for review see Bramhall et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such effects of noise which may be compounded by aging have been termed “hidden hearing loss” because they aren't detected by pure-tone audiometry (Liberman, 2020 ). Data from audiometrically normal adults shows that people with smaller auditory nerve or subcortical responses perform relatively poorly on hearing speech in the presence of background noise (Bharadwaj et al, 2015 ; Bramhall et al, 2015 ; Stamper and Johnson, 2015 ; Grant et al, 2020 ). However, this is still controversial as many studies in humans have failed to find significant relationships between speech perception and the amplitude of the auditory nerve action potential (Prendergast et al, 2017 ; Guest et al, 2018 ; for review see Bramhall et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen experiments found that isolated word recognition correlated with physiological CS proxies: twelve open-set word identification experiments presenting either words in steady-state noise or words that were sped up with reverberation added found correlations with ABR measures [four in Liberman et al (2016); three in Grant et al (2020)], with ABR and MEMR metrics [three in Mepani et al (2020)], or with EFRs (three in Mepani et al (2021)], and one using closed-set identification of words in noise with reverberation found a correlation with MEMR thresholds (Shehorn et al 2020). Liberman et al (2016) additionally observed significant relationships between word identification scores and noise exposure history.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Given that most patients seeking audiological help struggle in listening environments with back-ground noise, considerable effort has been directed to examine associations between risk factors for CS (i.e., NE history, or age), and suprathreshold hearing in noise. Such investigations have yielded mixed results (Bharadwaj et al, 2015; Prendergast et al, 2017; Bramhall et al, 2017; Yeend et al, 2017; Grant et al, 2020), perhaps because they have been hampered by multiple sources of variability (Bharadwaj et al, 2019). First, individuals with a history of greater NE and more advanced age tend to also have greater audiometric threshold elevations making it difficult to accurately estimate the effects attributable to CS.…”
Section: Introductionmentioning
confidence: 99%